Distribución geográfica del género Pimeliaphilus Trägårdh (Acari: Prostigmata) asociados a triatominos (Hemiptera: Reduviidae) - Martí, Gerardo Aníbal (2017)
A list of species of the genus Pimeliaphilus Trägårdh, associated with different species of american triatomines is provided, including their respective geographical coordinates. Bibliographic compilation and field work were carried out to incorporate new reports. The geographical distribution of Pimeliaphilus triatomae Cunliffe is extended, with two new reports for the province of Chaco (Argentina) and the host range is also extended, being the first time it is found associated with Triatoma delpontei Romaña & Abalos.